Comparative study of catalytic activities among transition metal-doped IrO2 nanoparticles. Issue 1 (December 2018) - Lee, Hangil; Kim, Joo; Lee, Si; Hong, Jung; Kim, Namdong; Baik, Jaeyoon; Hwang, Yun
Abstract Catalytic activities of transition metal-doped IrO2 nanoparticles (TM-IrO2 NPs; TM = Cr, Mn, Fe, Co, or Ni) are compared for various oxidation reactions such as electrochemical oxygen evolution reaction (OER), gas-phase photo-oxidation of thiol function group, and CO oxidative conversion. Here, we discovered a series of TM-IrO2 catalysts have a common activity trend for these oxidation reactions, and their activities are closely related with modified electronic states of IrO2, strongly affected by the types of the transition metal across the periodic table. For all oxidation reactions, Cr- and Mn-IrO2 achieved the highest oxidation catalytic activity, and sequentially decreased activities were obtained with Fe, Co, and Ni doped IrO2 . For instance, the highest OER activity was achieved by Cr or Mn doping exhibiting the smallest overpotential η = 275~230 mV at 10 mA/cm2, while Ni-IrO2 showed rather larger overpotential (η = 347 mV) even compared with non-doped IrO2 (η = 314 mV). Scanning transmission X-ray microscopy and high-resolution photoemission spectra of TM-IrO2 indicated dopant metals modified the Ir-O interaction and thus increasing oxygen vacancy defects in IrO2 . Strongly positive correlation was observed between the catalytic activities and vacancy states. The amount of defect related signals was observed the most for Cr- or Mn-IrO2, less so for Fe- or Co-IrO2, and unnoted for Ni-IrO2 compared with bare IrO2 . Based on these catalytic activities and surface spectroscopic analysis results, vacancy defects induced by doping in TM-IrO2 NPs are proposed to contribute to enhance the oxidation activities.